2011
DOI: 10.3109/0284186x.2010.512922
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and incidence trends of hydatidiform mole in Sweden 1973–2004

Abstract: The incidence of HM in Sweden has increased over time, and is characterized by a bimodal pattern with distinctive peaks in the youngest and oldest women of reproductive age. More than one third of all women registered with choriocarcinoma had a previous diagnosis of HM. Despite mandatory reporting, there was evidence of underreporting of HM to the SCR that remained virtually unchanged over calendar time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
3
22
1
Order By: Relevance
“…This was consistent with findings observed in other studies 9,17,18 . However, contrarily to other studies which also showed the risk to be increased at an age above 40 years, such pattern was not observed in this study, possibly because in our community, by the age of 40 years, most women have completed their family.…”
Section: Discussionsupporting
confidence: 83%
“…This was consistent with findings observed in other studies 9,17,18 . However, contrarily to other studies which also showed the risk to be increased at an age above 40 years, such pattern was not observed in this study, possibly because in our community, by the age of 40 years, most women have completed their family.…”
Section: Discussionsupporting
confidence: 83%
“…19 Another different situation was found in the Netherlands where incidence rates of HM increased until 2001 (+0.091 per year; 95% confidence interval (CI), 0.081Y0.101), after which the incidence rate remained constant (increase per year, j0.010; 95% CI, j0.045 to 0.024). 20 The reasons for these geographical differences remain unclear.…”
Section: Discussionmentioning
confidence: 96%
“…No change in the trend for the age at which complete molar pregnancy occurs was observed; most women get pregnant between the age of 20 and 30 years, so it is natural for cases of complete hydatidiform moles to be concentrated in this age group. 12,13 The greater availability of obstetric diagnostic techniques including sensitive ultrasound and hCG measurement and the more widespread availability and utilization of antenatal care likely contributed to complete molar pregnancy being diagnosed at an increasingly early gestational age, basically within the first trimester. 5Y7,12Y22 Early diagnosis has reduced the clinical complications of molar pregnancy, 16,17,23,24 enabling many patients to be diagnosed even before they have symptoms.…”
Section: Discussionmentioning
confidence: 99%